Exogenously Applied Plant Growth Regulators Affect Heat‐Stressed Rice Pollens. (31st July 2015) - Fahad, S.; Hussain, S.; Saud, S.; Khan, F.; Hassan, S.; Amanullah,; Nasim, W.; Arif, M.; Wang, F.; Huang, J.
Abstract: Increasing temperature due to global warming has emerged one of the gravest threats to rice production. This study examined the influence of high temperature and exogenously applied plant growth regulators on pollen fertility, anther dehiscence, pollen germination and metabolites synthesis in pollens of two rice cultivars (IR‐64 and Huanghuazhan (HHZ)). Plants were subjected to high day temperature (HDT), high night temperature (HNT) and control temperature (CT) in controlled growth chambers. Four different combinations of ascorbic acid (Vc), alpha‐tocopherol (Ve), brassinosteroids (Br), methyl jasmonates (MeJA) and triazoles (Tr) were used along with a nothing applied control. Our results depicted that high temperature severely reduced the pollen fertility, anther dehiscence, pollen retention, germination and metabolites synthesis in pollens of both rice cultivars. Nonetheless, exogenous application of various plant growth regulators assuaged the adverse effects of high temperature and Vc + Ve + MeJA + Br was found the best combination than the other treatments for every studied characteristic. The HNT posed more negative effects than the HDT. Variations were also apparent between cultivars and HHZ performed better than IR‐64 under high‐temperature stress, with higher pollen fertility, better anther dehiscence, and greater pollen retention and germination rates. The greater tolerance of HHZ to high temperature was related with the higher synthesis of metabolites in this cultivar.